2003
DOI: 10.1002/jsfa.1563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of weaning foods from Glyricidia and Leucaena leaf protein concentrates and some commercial brands in Nigeria

Abstract: Three studies were conducted to evaluate the nutritive potential of Glyricidia leaf protein concentrate (GLPC) and Leucaena leaf protein concentrate (LLPC) in infant weaning foods. The first two trials evaluated 10 laboratory-formulated weaning foods, in which soybean meal (SBM) was replaced at levels of 0, 25, 50, 75 and 100% with either GLPC or LLPC, and subsequently compared them nutritionally with three commercial weaning foods (coded CFB, CFC and CFN) currently on sale in Nigeria in a 28 day feeding trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The apparent differences in the amino acid composition might be due to the use of leaves of differing age and antecedents, or different processing techniques, as from real species differences (Pirie, 1979). Feeding experiments with chickens, mice, pigs and rats showed that LPC was safe and nutritionally useful (Pirie, 1979;Aletor, 2003 and2004). Four human trials have been published.…”
Section: Mineralmentioning
confidence: 99%
“…The apparent differences in the amino acid composition might be due to the use of leaves of differing age and antecedents, or different processing techniques, as from real species differences (Pirie, 1979). Feeding experiments with chickens, mice, pigs and rats showed that LPC was safe and nutritionally useful (Pirie, 1979;Aletor, 2003 and2004). Four human trials have been published.…”
Section: Mineralmentioning
confidence: 99%
“…leaf meals) in place of the relatively expensive conventional feeds for feeding monogastric animals is becoming popular in the tropics. This is primarily due to the erratic supply and high cost of conventional feedstuffs and secondarily because of rapid plant growth when water is available and the relatively low cost of these leaf meals, which are mainly from tropical legumes and browse plants (Agbede and Aletor, 2003). Therefore, leaf meals are included in livestock feed to offset the high cost of conventional protein sources and improve profit margin (Nodu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Water absorption, holding or binding capacity (WAC) may be defined as ability of food material to hold its own and added water during application of forces and heating. Water absorption is due to its dipolar nature so that proteins with more charged amino acids tend to absorb more water than proteins with uncharged amino acids [9] [32]. Low water absorption capacity Feregede compared to others may be attributed to decreased charge on its protein.…”
Section: Resultsmentioning
confidence: 99%
“…They are also explored more in the developed countries as ingredients primarily to provide a variety of functional properties, including desirable structure, texture, flavour, and colour characteristics in formulated food products [6] [7]. They are widely used in high protein foods including dairy foods, nutritional supplements, meat systems, infant formulas, nutritional beverages, cream soups, sauces and snacks and also as a protein source in milk replacers [8] [9]. In this respect, the edible bean types appear to be the most explored among the beans.…”
Section: Introductionmentioning
confidence: 99%